The Effectiveness of Inquiry-Based Learning Instrument to Enhance Student’s Critical Thinking Skills - Nanda Intan Maharani; I Wayan Dasna; Candra Utama (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The limitations of inquiry-based learning tools have an impact on the low critical thinking skills of elementary students in science learning. This study aims to examine the effectiveness of inquiry-based learning tools to improve critical thinking skills. The study design is a quasi nonequivalent control group experiment. The experimental class was treated with inquiry-based learning devices, the control class was implemented with STAD-based learning devices. The population and sample in this study were students in grades IVA and IVB at SDN Kepanjen 2 and SDN Panggungrejo 4. This study was conducted for one month from August to September 2022. The instrument used was a critical thinking skills test. The validity test is calculated based on the Aiken index. Data were analyzed based on the pair t-test. The results of this study indicate a very significant difference in students' critical thinking skills. The average score of students' critical thinking before the use of inquiry learning tools in the experimental class was 53.59 and after being used was 82.44. Control group students have an average critical thinking ability of 42.35 and thereafter 59.88. There are factors that affect the effectiveness of inquiry-based learning tools including the validity of the device, the difference in the average score of critical thinking skills which is very significant for students in the experimental and control groups, the responses of students and teachers, and the implementation of learning. In conclusion, instructional inquiry tools are effective for improving critical thinking skills. This study recommends the development of inquiry-based learning tools to improve students' critical thinking skills.